Peranan Zakat, Infak Dan Sedekah (ZIS) Dalam Upaya Meningkatkan Perekonomian Masyarakat Kota Metro - Mardiantari, Ani (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2019)
Zakat, infaq and almsgiving is one of the worship in Islam to seek pleasure from Allah SWT. In Islam besides worshiping zakat, infaq and almsgiving are also effective solutions for poverty alleviation. Therefore a zakat, infaq and alms management body is needed which has a good management mechanism and has an optimal role in efforts to improve the economy in the community. LAZISNU Metro City was formed in order to maximize the management of zakat and maximize the increase in the economy of the community in Metro City. The results of this study indicate that the zakat management mechanism that exists in LAZISNU Metro City is quite good, but there are still some parts that are not maximal due to the obstacles faced. The role of zakat, infaq and almsgiving in an effort to improve the economy of the community in Metro City runs in the form of consumptive assistance and productive assistance. The implementation is carried out based on Islamic law and the Law. Therefore LAZISNU Metro City needs to continue to evaluate in order to achieve a maximum role in an effort to improve the economy of the community in Metro City.